1999
DOI: 10.1002/jor.1100170408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically modulated cartilage growth may regulate joint surface morphogenesis

Abstract: The development of normal joints depends on mechanical function in utero. Experimental studies have shown that the normal surface topography of diarthrodial joints fails to form in paralyzed embryos. We implemented a mathematical model for joint morphogenesis that explores the hypothesis that the stress distribution created in a functional joint may modulate the growth of the cartilage anlagen and lead to the development of congruent articular surfaces. We simulated the morphogenesis of a human finger joint (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…The direct connection between local mechanical stress and cartilage thickness has not been reported in the literature, but computer simulation studies (Carter and Beaupre, 2001;Heegaard et al, 1999) and cell experimental studies (Smith et al, 1996(Smith et al, , 2000 support these results. Heegaard et al and Carter et al suggested that cartilage growth and morphology is regulated by hydrostatic pressure and octahedral shear stress (Carter and Beaupre, 2001;Heegaard et al, 1999). Smith et al showed that the chondrocyte metabolism varies according to the type of stresses and intermittent hydrostatic pressure increase type II collagen and aggrecan mRNA expression (Smith et al, 1996(Smith et al, , 2000.…”
Section: Article In Pressmentioning
confidence: 97%
See 1 more Smart Citation
“…The direct connection between local mechanical stress and cartilage thickness has not been reported in the literature, but computer simulation studies (Carter and Beaupre, 2001;Heegaard et al, 1999) and cell experimental studies (Smith et al, 1996(Smith et al, , 2000 support these results. Heegaard et al and Carter et al suggested that cartilage growth and morphology is regulated by hydrostatic pressure and octahedral shear stress (Carter and Beaupre, 2001;Heegaard et al, 1999). Smith et al showed that the chondrocyte metabolism varies according to the type of stresses and intermittent hydrostatic pressure increase type II collagen and aggrecan mRNA expression (Smith et al, 1996(Smith et al, , 2000.…”
Section: Article In Pressmentioning
confidence: 97%
“…During endochondral growth and ossification of bone rudiments, subchondral growth fronts under articular cartilage advance toward bone ends, forming the shape of the bone (Carter and Beaupre, 2001;Heegaard et al, 1999). Also, cartilage contact geometry, along with joint loading, can play an important role in determining local tissue stress (Han et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This surface is greatly influenced by hydrostatic pressures generated during function due to joint loading (Beaupre et al 2000;Carter et al 1987;Smith et al 1992). Animal experiments and clinical studies with altered joint load (increased or decreased) support a causal relationship between cartilage function and form (Heegaard et al 1999;Pirttiniemi and Kantomaa 1998). While augmenting the functional loading of joints causes an increase in articular cartilage thickness, immobilization leads to a thinning of articular cartilage.…”
Section: Introductionmentioning
confidence: 93%
“…These interactions led to the theoretical concepts of mechanobiology [4,7]. The stress and strains applied to the precursor cells induce specific biological responses at all levels of the regenerating skeletal structure, from the molecular level of its extracellular matrix [9,20] to its macroscopic morphology [4,17].…”
Section: Introductionmentioning
confidence: 99%